Assessing the hydraulic performance of bamboo logs in riverbank stabilization: case study of Sundarbans, India. Issue 1 (2nd January 2021) - Das, Vikas Kumar; Hansda, Sunil; Debnath, Koustuv; Chaudhuri, Susanta; Mazumder, Bijoy S.
ABSTRACT: Human settlements in the Sundarbans deltaic region of India have adopted a method of erecting embankments along the riverside to prevent river water from spilling over into the colonized areas. These embankments develop undercuts at the toe region that lead to failure from the swirling currents coupled with tidal surges and strong winds. To protect the embankment from erosion, the embankment face is covered with bamboo logs, as bamboo is easily available locally and is economically viable. However, from field investigations the use of bamboo logs for the prevention of embankment erosion is found to be ineffective in the Sundarbans region. The present investigation was carried out to develop insight into why the use of bamboo logs for embankment protection does not represent an optimal solution for bank stabilization. The current work emphasizes an appraisal of the turbulent flow characteristics in proximity to the bamboo logs and sediment bank interface.